IMPROVING THE STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT BY APPLYING MIND MAPPING TECHNIQUE - Frida Dian Handini (UIN Sumatera Utara, 2019)
This study was aimed at improving the students’ achievement in writing procedure text by applying mind mapping technique by conducting classroom action research. The subjects of this research were the students of grade X SMA Kebangsaan Medan. The number of the students was 15 students. The data were analyzed by using quantitative and qualitative procedures. The quantitative data were taken from students’ scores in writing procedure text. Then the qualitative data were taken from the questionnaire and observation sheets. There were two cycles in this research. The tests were done in three times. Before run the first cycle, the preliminary test was done. Based on the data analysis, the mean of the students score in preliminary test was 47.8, in cycle I was 64.6, and in cycle II was 72.8. The conclusion is not only mind mapping technique significantly improves the students’ achievement in writing procedure text, but also the students understanding about procedure text.